Composition of the main dominant pigments from potential two edible seaweeds - Brotosudarmo, Tatas Hardo Panintingjati; Limantara, Leenawaty; Indrawat, Renny; Adhiwibawa, Marcelinus Alfasisurya Setya; Indriatmoko , Shioi, Yuzo; Heriyanto (2018)
Two seaweed species - Kappaphycus alvarezii (Rhodophyta) and Padina australis (Phaeophyta) - have been commercially viable raw materials for the food industry. Despite their usefulness as sources of carrageenan and alginate, there is little information concerning their chlorophylls and carotenoids. Composition and quantification of the chlorophylls and carotenoids in K. alvarezii var. brown and P. australis were studied using reverse-phase high-performance liquid chromatography (RP-HPLC) with a recently developed 3D-multi-chromatogram analysis method. Identification of the most dominant pigments was confirmed by mass spectrometry using positive electron spray ionization. Samples were collected from three different locations in Indonesia (Jepara, Madura, and Maluku). A total of 39 pigments were found from the crude extracts of K. alvarezii and P. australis, and the four main dominant pigments (chlorophyll a, Î²-carotene, fucoxanthin, and zeaxanthin) were quantified by recently developed 3D-multi-chromatogram analysis method. Both seaweeds in three locations had almost similar pigment composition and only a small variation on minor pigments, except for the Maluku Island samples. The relationship between pigment concentration and environmental factor of solar irradiation was investigated using the pigment ratio between chlorophyll a and main carotenoids. The effect of solar irradiance on pigment formation is discussed.